SURVEILLANCE OF β-LACTAMASE GENES OF SALMONELLA FROM CHICKEN IN WET MARKETS OF METRO MANILA, PHILIPPINES - Miles Madayag; Rance Derrick Pavon; Jonah Feliza Mora; Khristine Balaga; Windell Rivera (BIOTROPIA, 2024)
Article Highlights- blaCTX-M gene in 24.7% while blaTEM gene in 11.2% of Salmonella isolates.- Coexistence of blaCTX-M groups II and IV in all blaCTX-M-positive isolates.- Dominance of blaCTX-M corroborated with phenotypic β-lactam resistances.- blaCTX-M-positive isolates had extended-spectrum β-lactamase and multidrug resistance. AbstractSalmonella sp. is a foodborne pathogenic bacterium causing millions of cases with hundred thousand death incidents. Infection by Salmonella can diversely manifest as gastroenteritis, bacteremia, and enteric fever. Salmonella can be transmitted through direct consumption of contaminated foods especially animal-based foods, such as chicken meat and its derivatives. Over the years, antimicrobial resistance (AMR) and diverse β-lactamase (bla) gene-carrying Salmonella strains have been reported. These facts are alarming given that cephalosporins are a major class of β-lactam antibiotics used in clinical settings. Hence, the main objective of this study was to molecularly detect the occurrence of different bla genes by Polymerase Chain Reaction (PCR) and profile the phenotypic antimicrobial susceptibility of Salmonella collected from various chicken sample types in wet markets of Metro Manila, Philippines. Of the 89 Salmonella isolates, blaCTX-M had the highest occurrence, detected in 22 isolates (24.7%), while blaTEM was detected in 10 isolates (11.2%). Genotypic and phenotypic resistance corroboration was observed in nearly all blaCTX-M-positive Salmonella tested, with all strains showing resistance to ampicillin and nitrofurantoin (100%) and 21 out of 22 (95.5%) exhibiting resistance to both non-extended and extended-spectrum cephalosporins. In addition, blaCTX-M groups II and IV genes were co-detected and multidrug resistance (MDR) profiles were also observed in all blaCTX-M-positive isolates. The high AMR patterns of Salmonella isolates suggest potential threats to food safety and public health. Additionally, the corroboration of phenotypic and genotypic resistance and the high occurrence of MDR among Salmonella isolates highlight the importance of continued surveillance of AMR genes and regulation of antimicrobial use to combat AMR.